NKB cells: A double-edged sword against inflammatory diseases - Tandel, Nikunj; Negi, Sushmita; Tyagi, Rajeev K. (Frontiers in Immunology, 2022)
Interferon-γ (IFN-γ)-producing natural killer (NK) cells and innate lymphoid cells (ILCs) are shown to activate the immune system in response to the pathogenic invasion, but priming of NKs and ILCs during infections is yet to be fully understood. Further, a novel lymphocyte subpopulation referred to as “natural killer-like B (NKB) cells” is seen in the spleen and mesenteric lymph nodes (MLNs) during infectious and inflammatory pathologies. Moreover, production of IL-18 and IL-12 during the early phase of infection differentiates NKB cells from NK and B cells. Also, NKB cells play key role in clearing microbial infections. In addition, NKB cells contribute to the inflammatory responses during infectious and inflammatory diseases. Hence, pathogenic role of NKB cells during the disease pathogenesis needs to be uncovered. Overall, the in-depth understanding of novel NKB cells could pave the way to develop an effective drug and vaccine therapeutics for infectious and inflammatory diseases.